Effect of weight loss, with or without exercise, on body composition and sex hormones in postmenopausal women: the SHAPE-2 trial. Issue 1 (December 2015) - van Gemert, Willemijn; Schuit, Albertine; van der Palen, Job; May, Anne; Iestra, Jolein; Wittink, Harriet; Peeters, Petra; Monninkhof, Evelyn
Abstract Introduction Physical inactivity and overweight are risk factors for postmenopausal breast cancer. The effect of physical activity may be partially mediated by concordant weight loss. We studied the effect on serum sex hormones, which are known to be associated with postmenopausal breast cancer risk, that is attributable to exercise by comparing randomly obtained equivalent weight loss by following a hypocaloric diet only or mainly by exercise. Methods Overweight, insufficiently active women were randomised to a diet (N = 97), mainly exercise (N = 98) or control group (N = 48). The goal of both interventions was to achieve 5–6 kg of weight loss by following a calorie-restricted diet or an intensive exercise programme combined with only a small caloric restriction. Primary outcomes after 16 weeks were serum sex hormones and sex hormone-binding globulin (SHBG). Body fat and lean mass were measured by dual-energy X-ray absorptiometry. Results Both the diet (−4.9 kg) and mainly exercise (−5.5 kg) groups achieved the target weight loss. Loss of body fat was significantly greater with exercise versus diet (difference −1.4 kg, P < 0.001). In the mainly exercise arm, the reduction in free testosterone was statistically significantly greater than that of the diet arm (treatment effect ratio [TER] 0.92, P = 0.043), and the results were suggestive of a difference for androstenedione (TER 0.90, P = 0.064) and SHBG (TER 1.05, P = 0.070). Compared with the control arm, beneficial effects were seen with both interventions, diet and mainly exercise, respectively, on oestradiol (TER 0.86, P = 0.025; TER 0.83, P = 0.007), free oestradiol (TER 0.80, P = 0.002; TER 0.77, P < 0.001), SHBG (TER 1.14; TER 1.21, bothP < 0.001) and free testosterone (TER 0.91, P = 0.069; TER = 0.84, P = 0.001). After adjustment for changes in body fat, intervention effects attenuated or disappeared. Conclusions Weight loss with both interventions resulted in favourable effects on serum sex hormones, which have been shown to be associated with a decrease in postmenopausal breast cancer risk. Weight loss induced mainly by exercise additionally resulted in maintenance of lean mass, greater fitness, greater fat loss and a larger effect on (some) sex hormones. The greater fat loss likely explains the observed larger effects on sex hormones. Trial registration ClinicalTrials.gov identifier:NCT01511276 . Registered on 12 January 2012.